TRANSLATION OF IRONY («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The aim of this study was to identify the methods of translation utilized in translating ironic and sarcastic statements in the novel titled Pride and Prejudice and to assess the resulting translation quality.   This study followed a qualitative approach and examined utterances in the novel in both English (source language) and Indonesian (target language).   The focus of the study was on the final translation product, as the research questions were centered around written texts containing ironic and sarcastic statements.
Keywords: literary definitions, intelligence, comparative analysis, literal translation, providing access.